Welche Bedeutung haben Unternehmenscharakteristika und regionales Umfeld für die Beschäftigungsdynamik? Eine mikroökonometrische Analyse für das ostdeutsche Verarbeitende Gewerbe - Fabian Steil; Elke Wolf (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1997)
In this paper, we analyse the influence of firm characteristics and the regional environment on employment growth of East German manufacturing firms between 1992 and 1996. Our results confirm the negative impact of firm size and age on employment growth found in various studies for several developed economies. An additional negative effect far firms which have emerged from former state-owned establishments can only be observed for firms with more than nine employees. Our analysis also shows some evidence that there exists a positive influence of localization economies on the firm specific growth rate of employment. Furthermore. the regional wage rate influences the growth rate in the expected way.
Keywords: 330